2011
DOI: 10.1007/s00439-010-0942-0
|View full text |Cite
|
Sign up to set email alerts
|

Genes in the insulin and insulin-like growth factor pathway and odds of metachronous colorectal neoplasia

Abstract: Insulin and insulin-like growth factor (IGF) genes are implicated in colorectal carcinogenesis. Gene-by-gene interactions that influence the insulin/IGF pathways were hypothesized as modifiers of colorectal neoplasia risk. We built a classification tree to detect interactions in 18 IGF and insulin pathway-related genes and metachronous colorectal neoplasia among 1,439 subjects pooled from two chemoprevention trials. The probability of colorectal neoplasia was greatest (71.8%) among carriers of any A allele for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…A manual search of reference lists captured nine further studies that met our entry criteria . Thus, 55 studies published between 1987 and 2016 were included in the review (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
“…A manual search of reference lists captured nine further studies that met our entry criteria . Thus, 55 studies published between 1987 and 2016 were included in the review (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to assess the association of INSR polymorphisms with childhood obesity. Previously, studies on association of INSR gene polymorphisms with hypertension (Kuo et al (LeRoy et al 2011;Cox et al 2009;Wang et al 2007) and type 2 diabetes (Bodhini et al 2012) have been reported but not with obesity. Insulin signalling plays a crucial role in lipid storage and regulation of glucose homeostasis in adipose tissue (Blüher et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Thus far, with the improvement of living standards in more and more developing countries, obesity and lifestyle-related cancers have been on the increase [ 33 , 34 ]. IGF1 has been reported to relate to be associated with the cancer susceptibility, especially cancers caused by obesity, due to its important role in cell proliferation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%